ADHD in Preschool: Approaches and Teacher Training - Singh, Ajay; Squires, Jane (Journal of the American Academy of Special Education Professionals, 2014)
Due to the prevalence of ADHD, there is a need for early intervention at the preschool level to improve children’s chance of academic success in later years. Yet few preschool teachers are trained to meet the challenges children with ADHD present. This paper gives a rationale and curriculum for teacher training in ADHD, with an emphasis on Social Emotional Learning, Parent Training, and Field Experience with a Mentor.